Pola Komunikasi Organisasi IMMUBA Dalam Mempertahankan Solidaritas Keanggotaan - Ahmad Zamzami; Achmad Syarifuddin; Sri Hertimi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the organizational communication patterns of IMMUBA in maintaining membership solidarity. Organizational communication plays an important role in building harmonious relationships, strengthening a sense of togetherness, and maintaining members’ commitment within an organization. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The informants consist of IMMUBA administrators and active members involved in organizational activities. Data analysis techniques follow the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the communication patterns implemented in IMMUBA include vertical, horizontal, and informal communication. Vertical communication functions in delivering information between administrators and members, while horizontal communication strengthens relationships among members. In addition, informal communication plays a significant role in creating emotional closeness and reinforcing solidarity. Membership solidarity is also supported by open communication, active participation, and collective activities that foster togetherness. Therefore, effective communication patterns are the key to maintaining membership solidarity within the IMMUBA organization.